Digital Literacy as an Action Plan to Prevent Online Fraud Using the Triangle Scheme in the Jurisdiction of Makassar Police Headquarters - Rinal Krishna Triananda; Basir S.; Muhamad Erza Aminanto (Transpublika Publisher, 2025)
This research aims to evaluate the effectiveness of preventive strategies implemented by the Makassar Police Headquarters (Polrestabes) in handling triangle scheme online fraud, a form of cybercrime that is increasingly prevalent alongside the rise in online transaction activities among the public. A qualitative approach with case study methodology is used to examine in depth the digital literacy strategies initiated by Makassar Police Headquarters, including collaboration between internal functional units and synergy with external stakeholders. Research findings indicate that although institutional frameworks and legal regulations are available, the implementation of digital literacy programs still faces constraints including budget limitations, gaps in digital technology mastery, and suboptimal reach of educational programs to peripheral areas. SWOT analysis and application of social system theory, community policing, and digital literacy implementation models indicate the need for strengthening human resource capacity, diversifying socialization methods, and establishing cross-sector collaborative forums to strengthen the community's digital security ecosystem. This research recommends the formulation of strategic policies that integrate digital literacy with law enforcement based on the Information and Electronic Transaction Law, Criminal Code, as well as personal data protection and consumer protection regulations. With a comprehensive and sustainable approach, prevention of triangle scheme online fraud can be optimized as part of the national cyber security strategy.